2021
DOI: 10.1016/j.cmi.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome and safety of bedaquiline-containing regimens for treatment of MDR- and XDR-TB in China: a multicentre study

Abstract: Conclusion: Bedaquiline, when included in background regimens for treatment of MDR-TB and XDR-TB patients in China, was safe and associated with a high rate of culture conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 18 publications
2
44
1
7
Order By: Relevance
“…A retrospective study was conducted in 13 TB specialized hospitals across China of MDR-TB patients receiving BDQ-containing regimens, of whom 91% had prior LZD treatment histories. Sputum specimens were collected from patients at baseline, 2, 4, 8, 12, 16, 20, and 24 weeks after treatment initiation, as previously reported ( Gao et al, 2020 ). MTB isolates collected at baseline and at final follow-up for each patient were recovered by culturing specimens on Löwenstein-Jensen medium for 4 weeks at 37°C prior to in vitro drug susceptibility testing.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective study was conducted in 13 TB specialized hospitals across China of MDR-TB patients receiving BDQ-containing regimens, of whom 91% had prior LZD treatment histories. Sputum specimens were collected from patients at baseline, 2, 4, 8, 12, 16, 20, and 24 weeks after treatment initiation, as previously reported ( Gao et al, 2020 ). MTB isolates collected at baseline and at final follow-up for each patient were recovered by culturing specimens on Löwenstein-Jensen medium for 4 weeks at 37°C prior to in vitro drug susceptibility testing.…”
Section: Methodsmentioning
confidence: 99%
“…Despite limited data, we observed that a patient with resistance to both LZD and BDQ but susceptible to FQ experienced treatment failure. In a recent BDQ clinical trial, the administration of BDQ-containing regimens provides particular benefit for pre-XDRand XDR-TB patients [15]. On one hand, the existing evidence from studies confirmed BDQ as a cornerstone in the treatment of MDR-TB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that the rate of XDR-TB was noted in 6.8% of patients afflicted to MDR-TB, which was significantly decreased from 33.6% on the basis of previous definition. This low rate of XDR-TB was majorly attributed to relatively late introduction of BDQ and LZD for clinical management of MDR-TB in China, thereby preventing accumulation of drug resistant mutations [15]. Consequently, this holds great promise for MDR-TB treatment with WHO-endorsed regimens containing BDQ-LZD combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last year, several reports have shown the potential of combining BDQ other highly bactericidal drugs in order to shorten treatments, showing added cost-effectiveness [42][43][44][45][46][47]. Such evidence has moved the WHO to recommend shorter regimens based on a drug combination that takes into account different characteristics, especially oral administration and bactericidal/sterilizing activity (Table 1) [5].…”
Section: Clinical Efficacymentioning
confidence: 99%